Revision of the cricket genus Cardiodactylus (Orthoptera, Eneopterinae, Lebinthini): the species from both sides of the Wallace line, with description of 25 new species - Robillard, Tony; Gorochov, Andrej V.; Poulain, Simon; Suhardjono, Yayuk R. (Zootaxa, 2014)
The genus Cardiodactylus is the most speciose and widely distributed genus of the cricket subfamily Eneopterinae and of the Lebinthini tribe. Along with diverse acoustic features, this genus is also characterized by a wide distribution area running from Japan to Southeast Asia, Northern Australia and in many archipelagos in the Western Pacific, with a high contrast in species distributions. In this paper we start revising Cardiodactylus by focusing on the western region of its wide distribution and the Novaeguineae species group. We describe 25 new species of Cardiodactylus, redescribe 3 species and bring new signalizations for 5 species. Whenever possible, information is provided about species distribution, male calling song and male and female genitalia, forewing venation and habitat.